Common Mechanisms Underlying Refractive Error Identified in Functional Analysis of Gene Lists From Genome-Wide Association Study Results in 2 European British Cohorts - Hysi, Pirro G. (2014)
IMPORTANCE: To date, relatively few genes responsible for a fraction of heritability have been identified by means of large genetic association studies of refractive error. OBJECTIVE: To explore the genetic mechanisms that lead to refractive error in the general population. DESIGN, SETTING, AND PARTICIPANTS: Genome-wide association studies were carried out in 2 British population-based independent cohorts (N = 5928 participants) to identify genes moderately associated with refractive error. MAIN OUTCOMES AND MEASURES: Enrichment analyses were used to identify sets of genes overrepresented in both cohorts. Enriched groups of genes were compared between both participating cohorts as a further measure against random noise. RESULTS: Groups of genes enriched at highly significant statistical levels were remarkably consistent in both cohorts. In particular, these results indicated that plasma membrane (P = 7.64 × 10(−30)), cell-cell adhesion (P = 2.42 × 10(−18)), synaptic transmission (P = 2.70 × 10(−14)), calcium ion binding (P = 3.55 × 10(−15)), and cation channel activity (P = 2.77 × 10(−14)) were significantly overrepresented in relation to refractive error. CONCLUSIONS AND RELEVANCE: These findings provide evidence that development of refractive error in the general population is related to the intensity of photosignal transduced from the retina, which may have implications for future interventions to minimize this disorder. Pathways connected to the procession of the nerve impulse are major mechanisms involved in the development of refractive error in populations of European origin.